2017
DOI: 10.1007/s10113-017-1245-y
|View full text |Cite
|
Sign up to set email alerts
|

Woody plant encroachment following grazing abandonment in the subalpine belt: a case study in northern Spain

Abstract: The montane and subalpine belts in European mountains were affected by intense land use/land cover changes during the 20th century. In the case of the subalpine belt, most European mountains were affected by complex deforestation processes from Neolithic times, leading to the expansion of summer grasslands to support grazing by transhumant sheep and goats flocks. This resulted in an altitudinal reduction of the tree line, and the occurrence of severe soil erosion and shallow landsliding. The intense livestock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 65 publications
2
31
0
3
Order By: Relevance
“…The last Spanish regions with high potential of future abandonment according to LUISA are placed mainly in the Central Pyrenees, northern part of the Iberian Range and the inner side of the Ebro basin (Huesca, Navarra, La Rioja, Zaragoza and Teruel) whilst less pronounced in the Catalan Prelitoral (Lleida, Barcelona and Tarragona). During the last decades, many studies were focused on these areas at plot, catchment, local or regional scale, mainly dealing with the hydrological, geomorphological or land-use change effects of land abandonment rather than, in most cases, the abandonment of agricultural use per se [20,29,[74][75][76][77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…The last Spanish regions with high potential of future abandonment according to LUISA are placed mainly in the Central Pyrenees, northern part of the Iberian Range and the inner side of the Ebro basin (Huesca, Navarra, La Rioja, Zaragoza and Teruel) whilst less pronounced in the Catalan Prelitoral (Lleida, Barcelona and Tarragona). During the last decades, many studies were focused on these areas at plot, catchment, local or regional scale, mainly dealing with the hydrological, geomorphological or land-use change effects of land abandonment rather than, in most cases, the abandonment of agricultural use per se [20,29,[74][75][76][77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…However, S. scardica is in vegetative growth and differentiates its inflorescence organs during spring and obviously receives competitiveness from the other highly dense plant species due to the absence of grazing at that time. On the other hand, grazing in subalpine Mediterranean ecosystems has been in constant decline over the last decades [58] and in some cases, such as Tetralofos in the present study, has been completely abandoned. The abandonment of grazing in these ecosystems results in shrub encroachment, the prevalence of competing species, and the reduction of diversity [58,59].…”
Section: Discussionmentioning
confidence: 59%
“…On the other hand, grazing in subalpine Mediterranean ecosystems has been in constant decline over the last decades [58] and in some cases, such as Tetralofos in the present study, has been completely abandoned. The abandonment of grazing in these ecosystems results in shrub encroachment, the prevalence of competing species, and the reduction of diversity [58,59]. It should be noticed that this was not the case in Tetralofos, where high floristic diversity was recorded.…”
Section: Discussionmentioning
confidence: 59%
“…The plant functional traits, which exist in various terrestrial plant species, can effectively signify shifts in ecosystem functions and processes (De Vries, Brown, & Stevens, ). In semiarid regions, N addition affects native grassland in the macro‐scale performance of ecosystems and the plant function at the micro‐scale (Sanjuán et al., ). Our results demonstrated that the aboveground biomass of L. chinensis tended to be larger under N addition compared with CK.…”
Section: Discussionmentioning
confidence: 99%